Assessing body position through experimental cremation: A pilot study using colorimetry and FTIR-ATR analyses - Paula Becerra Fuello; Javier Lescure; Aaron Lackinger; María Sedeño Ráez; Jesús Gámiz Caro; Gonzalo Aranda Jiménez (PLoS ONE, 2026)
This pilot study evaluates the feasibility and limitations of a multi-proxy approach for identifying potential indicators of horizontal positioning in cremated heads from archaeological, and to a lesser extent, forensic contexts. Two outdoor experimental cremations using fleshed and dry pig crania were conducted to evaluate the influence of pre-burning condition, vertical placement within the pyre and pyre dynamics on the expression of lateralised burning patterns. Combining macroscopic observations, fragmentation, colorimetric and Fourier-Transform Infrared Spectroscopy in Attenuated Total Reflectance (FTIR-ATR) mode, our preliminary observations suggest that lateralised differences in thermal exposure may be detectable under certain conditions. Significant differences (p-value < 0.005) were found between direct contact areas and indirect contact areas, with direct contact regions exhibiting lighter colouration and greater calcination. Higher crystallinity (IRSF) was also noted in direct contact areas, especially for the head placed on top of the pyre (Head 1). Inner surfaces consistently retained darker hues, indicating tissue shielding effects. Fleshed and dry elements also behaved differently: the dry cranium was less fragmented and with a more homogeneous colouration. As a small-scale experiment involving heterogeneous specimens and variable pyre dynamics, this study does not attempt to reconstruct body position but instead identifies methodological variables with potential for future replicated research. These preliminary results support the value of combining multi-proxy analyses such as colorimetry and FTIR-ATR for detecting specific burning patterns and inferring body position in cremation studies and provide a starting point for the refinement of methodology in future experimental works.